Analysis Of Taxpayer Compliance With The Optimization Of Rural And Urban Land And Building Tax Revenue In Class A Jonggol Regional Tax UPT - mulyawati, Evi; Indupurnahayu, Indupurnahayu; Hurriyaturrohman, Hurriyaturrohman (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2022)
This study analyzes the taxpayer compliance of Land and Building Tax at the Jonggol Class A Regional Tax UPT 2017-2020. This think about points to decide the level of citizen compliance, to decide the factors and strategies used to optimize P2 PBB revenue. This consider utilized expressive subjective strategy. Information gotten by perception, interviews, writing, and documentation. Thelevelof taxpayers compliance oflandand buildingatthe Class A Jonggol Regional Tax UPT is included in the non-compliance criteria with a proportion of not more than 60% every year from 2017 to 2020. There are internal factors and external factors that affect  Land and Building Tax revenue, such as economic conditions, taxpayer awareness of taxes, human resources for tax services, and others. To overcome these factors, several strategies were carried out such as mobile cars, online services, and others.